-3x + 6 + 15x =11x + 8 ie -3x + 15x - 11x = 8 - 6 ie x = 2
Set up the equation and solve: 15x - 8 - 3x = 16 (next add 8 to each side) 15x - 3x - 16 + 8 (next simplify) 12x = 24 (next divide both side by 12 to solve for x) x = 2
Sounds like a system of equations. Y + 5X = - 2 - 15X - 3Y = 6 substitution using first equation Y + 5X = - 2 Y = - 5X - 2 ==========insert into other equation as this is Y - 15X - 3(- 5X - 2) = 6 - 15X + 15X + 6 = 6 ========================This looks to be a dependent system that has an infinite number of solutions
3(2x - 1)(x - 2)
Do you mean? 3Y = - 15X + 6 Just divide all integers by 3 (3/3)Y = (- 15/3)X + 6/3 Y = - 5X + 2 ==============or. standard form 3Y = - 15X + 6 3Y + 15X = 6 ==============aY +bX = c
s=6
When X = 4, 15X = 15 * X = 15 * 4 = 60
15x-20y= 7 5y-3 +10x
x=6
12g-6=6+4=10g
The answer is 567. 2x189=378. 3x189=567.
6 = Henry (the) Eighth's Wives